La concepción de la pobreza en el modelo neoliberal. ¿Cómo entender la lucha contra la pobreza en México? - Czarnecki, Lukasz (Frontera Norte, 2017)
The concept of the poverty in the neoliberal model. How to understand the fight against poverty in Mexico?